ChemInform Abstract: Pd‐Catalyzed Oxidative Cross‐Coupling Between Two Electron Rich Heteroarenes. Issue 6 (11th February 2014) - He, Chun‐Yang; Wang, Zhen; Wu, Cai‐Zhi; Qing, Feng‐Ling; Zhang, Xingang
Abstract The title reaction of two heteroaromatic cross‐coupling partners with similar structures and electronic properties under mild conditions is achieved.